Burden-sharing and allocation criteria under the UN climate regime: neither fair nor effective - Britta Horstmann; Imme Scholz (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The United Nations Framework Convention on Climate Change (UNFCCC) calls on all parties to protect the climate system in accordance with their common but differentiated responsibilities and respective capabilities. This principle of equity was formulated at the United Nations Conference on the Environment and Development held in Rio de Janeiro in 1992 and still serves as the template for the development of criteria designed to ensure fair burden-sharing under the UN climate regime. Since then, however, the responsibilities and capabilities of countries have changed considerably with respect both to climate protection and to protection against the effects of climate change. Against this backdrop, it is clear that the current burden-sharing and financial transfer criteria are both unfair and ineffective from a climate policy viewpoint: unfair mainly when it comes to financing adaptation to climate change; ineffective in reducing greenhouse gas emissions. In the financing of adaptation measures, vulnerability to the consequences of climate change is the main allocation criterion under the climate regime. However, that criterion has yet to be applied in practice, there being no objective measure of the impact of climate change. Numerous normative decisions need to be made, but there is no sign of a consensus among either academics or politicians. As the Framework Convention and the Kyoto Protocol both fail to define vulnerability and particularly vulnerable countries, the Adaptation Fund and the planned Green Climate Fund, for instance, will be unable to allocate scarce resources equitably on the basis of the vulnerability criterion. Vulnerability is not currently considered when priorities are set for accessing adaptation financing under the UN climate regime. As regards climate protection, it is clear that global warming cannot be restricted to 2 °C if the burden is shared in accordance with the Kyoto Protocol. The division in 1992 of countries into those with and those without climate protection obligations has hitherto proved ineffective: traditionally large emitters have made little or no contribution to reducing emissions; major new emitters are under no obligation to do so. If the international community wants effective, equitable climate protection, it will have to stop dividing the world into two categories and instead specify new burdensharing and allocation criteria based on the principle of equity. That step was not taken in Copenhagen and, given its major implications, is unlikely to be taken in Durban. Does this mean that the question of equity is becoming a blind alley of international climate policy? The present analysis shows that, in a world still characterised by major disparities in levels of prosperity, differentiation is still needed if a fair, negotiated solution is to be found. It is equally clear, however, that the criteria for the implementation of the equity principle should be developed with each country's capabilities borne in mind. Where adaptation financing is concerned, this means distinguishing between developing countries according to their “response capacity”, that is, their ability to react to climate change. To reduce emissions, everyone should have the same emission rights within a fixed global carbon budget, and all countries should be under an obligation not to exceed their national budgets. In this way internationally comparable common standards would be set. Implementation would be supported by tradable rights and financial transfers.
Keywords: 330; Klimawandel